Contribution games and the end-game effect: When things get real - An experimental analysis - Ronen Bar-El; Yossi Tobol (Institute for the Study of Labor (IZA), 2013)
We conduct a contribution game for a real public good and show that when the contributors value the real public good highly, they increase their contributions in each round. Thus, contrary to previous literature, free riding decreases over rounds and the end-game effect is reversed.
Keywords: C72; C92; H41; 330; public goods experiment; end-game effect; free-riding